An audit into use of minimum dataset reporting of skin cancers in the North of England Cancer Network. Issue 1 (2015) - Barrett, Paul D.; Barrett, Hannah E.
Abstract: Aim: We report an audit of skin cancers reported by pathologists across the North of England Cancer Network. Method: We examined 386 reports to determine whether core data items recommended by the National Minimum dataset had been included in the pathology reports. Results: Only 115 of the 386 reports (30%) had all the expected data items compared to the expected standard of 90%. Melanoma reports were more often fully compliant (42%) compared with non-melanoma skin cancer (26%). Of 203 proforma reports, 112 were considered complete compared to only 3 of 183 free text reports. This confirms once again the value of a structured report in capturing all required core data items. The data items accounting for the majority of the deficiencies were tumour subtype, T stage and particularly risk status. Discussion: We consider the reasons behind the poor level of compliance and consider opportunities that may exist to aid pathologists in generating clinically more useful reports of skin cancers.